Bacterial aetiological agents of intra-amniotic infections and preterm birth in pregnant women - Mendz, George L.; Kaakoush, Nadeem O.; Quinlivan, Julie A. (Frontiers in Cellular and Infection Microbiology, 2013)
Infection-related preterm birth is a leading cause of infant mortality and morbidity; knowledge of bacterial populations invading the amniotic cavity and the routes of invasion is required to make progress in the prevention of preterm birth. Significant advances have been made in understanding bacterial communities in the vagina, but much less studied are intra-uterine bacterial populations during pregnancy. A systematic review of data published on the intra-uterine microbiome was performed; molecular information and summaries of species found in healthy individuals and in women with diagnosed infections served to construct a database and to analyse results to date. Thirteen studies fulfilled the review's inclusion criteria. The data of various investigations were collated, organised and re-analysed to achieve a more comprehensive understanding of microbial populations in the intra-amniotic space. The most common intra-amniotic bacterial taxa were species that can colonise the vagina in health and disease; there were others associated with the habitats of the mouth, gastrointestinal tract and respiratory tract. The results suggest a central role for the ascending route of infections during pregnancy, and points to a possible secondary contribution via haematogenous invasion of the intra-amniotic space. The census of the intra-uterine microbiome awaits completion.